Tracking the Real‐Time Evolution of a Writing Event: Second Language Writers at Different Proficiency Levels. Issue 2 (22nd January 2018) - Gánem‐Gutiérrez, Gabriela Adela; Gilmore, Alexander
Abstract: The current study focused on emergent processes during real‐time second language (L2) writing activity in an English as a foreign language university context, examining differences in these processes across individual capacities. Participants included 22 adult Japanese learners of L2 English and their tutor. The data were collected using digital screen capture and eye‐tracking technologies while the learners wrote a 35‐minute argumentative essay. Supplementary stimulated retrospective recalls were also conducted to document the learners' and the tutor's reflections on the writing event. Results revealed clear differences in L2 writing activity at different periods in time as well as differences in cognitive activity that appear to be mediated by L2 proficiency. Importantly, the obtained patterns differed depending on whether duration or frequency data were considered. These findings thus demonstrate the need to broaden the study of the temporal dimension of L2 writing and to consider more nuanced mixed‐methods approaches in future work.